Platelet Toll-Like Receptors Mediate Thromboinflammatory Responses in Patients With Essential Thrombocythemia - Marín Oyarzún, Cecilia P.; Glembotsky, Ana C.; Goette, Nora P.; Lev, Paola R.; De Luca, Geraldine; Baroni Pietto, María C.; Moiraghi, Beatriz; Castro Ríos, Miguel A.; Vicente, Angeles; Marta, Rosana F.; Schattner, Mirta; Heller, Paula G. (Frontiers in Immunology, 2020)
Essential thrombocythemia (ET) is comprised among chronic myeloproliferative neoplasms (MPN) and is caused by driver mutations in JAK2, CALR and MPL, which lead to megakaryocyte proliferation and prominent thrombocytosis. Thrombosis remains the main cause of morbidity in ET and is driven by the interplay between blood cells, the endothelium, the clotting cascade and host-derived inflammatory mediators. Platelet activation plays a key role in the thrombotic predisposition, although the underlying mechanisms remain poorly defined. In addition to their role in hemostasis, platelets participate in innate immunity and inflammation owing to the expression of toll-like receptors (TLR), which recognize inflammatory signals, triggering platelet functional responses. Considering the impact of inflammation on ET procoagulant state, we assessed the contribution of TLR2 and TLR4 to platelet hemostatic and inflammatory properties in ET patients, by using Pam3CSK4 and lipopolysaccharide (LPS) as specific TLR2 and TLR4 ligands, respectively. TLR2 ligation induced increased surface translocation of α-granule-derived P-selectin and CD40L, which mediate platelet interaction with leukocytes and endothelial cells, respectively, and higher levels of dense granule-derived CD63 in patients, whereas PAC-1 binding was not increased and LPS had no effect on these platelet responses. Platelet-neutrophil aggregate formation was elevated in ET at baseline and after stimulation of both TLR2 and TLR4. In addition, ET patients displayed higher TLR2- and TLR4-triggered platelet secretion of the chemokine RANTES (CCL5), whereas von Willebrand factor release was not enhanced, revealing a differential releasate pattern for α-granule-stored inflammatory molecules. TLR-mediated hyperresponsiveness contrasted with impaired or preserved responses to classic platelet hemostatic agonists, such as TRAP-6 and thrombin. TLR2 and TLR4 expression on the platelet surface was normal, whereas phosphorylation of downstream effector ERK1/2 was higher in patients at baseline and after incubation with Pam3CSK4, which may partly explain the enhanced TLR2 response. In conclusion, exacerbated response to TLR stimulation may promote platelet activation in ET, boosting platelet/leukocyte/endothelial interactions and secretion of inflammatory mediators, overall reinforcing the thromboinflammatory state. These findings highlight the role of platelets as inflammatory sentinels in MPN prothrombotic scenario and provide additional evidence for the close intertwining between thrombosis and inflammation in this setting.